2012
DOI: 10.1097/cad.0b013e328351f896
|View full text |Cite
|
Sign up to set email alerts
|

Growth-inhibitory and apoptosis-inducing effects of tanshinones on hematological malignancy cells and their structure–activity relationship

Abstract: This study has investigated the growth-inhibitory and apoptosis-inducing effects of dihydrotanshinone, tanshinone I, tanshinone IIA, and cryptotanshinone on hematological malignancy cell lines, aiming to explore their structure-activity relationship. The growth-inhibitory effects of the tanshinones on K562 and Raji cells were assessed using a modified MTT assay; the apoptosis-inducing effects were assessed by fluorescence microscopy and flow cytometry analysis. The changes in cellular morphology were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In the present study, dihydrotanshinone I exhibited the most notable cytotoxicity against the human cancer cell lines, followed by tanshinone I and cryptotanshinone. These results are consistent with previous reports, which indicated that dihydrotanshinone I possesses the most marked cytotoxic effect among the three tanshinones examined in numerous human cancer cell lines ( 14 , 29 , 30 ). As these three tanshinones possess similar chemical structures, the limited variations in these structures may be responsible for the differences in their cytotoxic effects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, dihydrotanshinone I exhibited the most notable cytotoxicity against the human cancer cell lines, followed by tanshinone I and cryptotanshinone. These results are consistent with previous reports, which indicated that dihydrotanshinone I possesses the most marked cytotoxic effect among the three tanshinones examined in numerous human cancer cell lines ( 14 , 29 , 30 ). As these three tanshinones possess similar chemical structures, the limited variations in these structures may be responsible for the differences in their cytotoxic effects.…”
Section: Discussionsupporting
confidence: 93%
“…As presented in Fig. 3B , the only structural differences among the three reference tanshinones are in aromatic rings A and C. A previous report indicated that the structure of ring A may contribute to the cytotoxic effect, resulting in the increased cytotoxic potential of dihydrotanshinone I and tanshinone I compared with cryptotanshinone, in terms of growth inhibition ( 29 ).…”
Section: Discussionmentioning
confidence: 83%
“…In agreement with our present study, other group also reported that CT treatment induced programmed cell death in various cancer cell lines. [ 11 16 17 ] These results suggest that CT can be a good inducer of apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 87%
“…Compound 7 is shikonin from Radix Arnebiae and was reported to possess anti-inflammatory activity [ 25 ]. Compound 8 is dihydrotanshinone I from Radix Salviae Miltiorrhizae and shows cytotoxicity against many types of cancer cells [ 26 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%